Materials matter: Understanding the importance of sociomaterial assemblages for OSCE candidate performance. Issue 8 (23rd March 2021) - Rees, Charlotte E.; Ottrey, Ella; Barton, Peter; Dix, Samantha; Griffiths, Debra; Sarkar, Mahbub; Brooks, Ingrid
Abstract: Introduction: The OSCE is a sociomaterial assemblage—a meshing together of human and material components producing multiple effects. Materials matter because they shape candidate performance, with potentially calamitous career consequences if materials influence performance unjustly. Although the OSCE literature refers to materials, few papers study the sociomateriality of OSCEs. Therefore, we explored OSCE stakeholders' talk about sociomaterial assemblages to better understand their importance for candidate performance. Methods: We conducted 15 focus groups with OSCE candidates (n = 42), examiners (n = 20) and simulated patients (n = 17) after an Australian postgraduate nursing OSCE. Sociomateriality informed our team‐based framework analysis of data. Results: Participants identified a multiplicity of OSCE materials (objects, technologies and spaces) thought to matter for candidate performance. Candidates' unfamiliarity with materials and missing or malfunctioning materials were reported to yield numerous negative impacts (eg cognitive overload, negative affect, time‐wasting), thereby adversely affecting candidate performance. Both examiners and candidates made micro‐adjustments to sociomaterial assemblages during the OSCE in order to make it work (eg candidates saying what they would do rather than doing it). Sometimes, such tinkering extended so far that sociomaterial assemblages were ruptured (eg examiners ignoring rubrics to help pass candidates), potentially influencing OSCE standardisation. Discussion: Our novel empirical study extends previous conceptual work by illustrating wide‐ranging sociomaterial assemblages influencing OSCE candidate performance. Further research is now needed employing sociomaterial approaches to further elucidate sociomaterial entanglements in diverse OSCEs. We encourage OSCE stakeholders to become more attuned to the productive nature of materials within all stages of OSCE design and implementation. Abstract : The authors demonstrate the extent to which materials really matter in shaping candidate performance in OSCEs